Separation of antioxidant and α-glucosidase inhibitory flavonoids from the aerial parts of Asterothamnus centrali-asiaticus. Issue 12 (18th June 2017) - Wang, Yan-Ming; Zhao, Jian-Qiang; Yang, Jun-Li; Tao, Yan-Duo; Mei, Li-Juan; Shi, Yan-Ping
Abstract: A new flavonoid, along with 16 known ones, was separated from the aerial parts of Asterothamnus centrali - asiaticus . Their structures were elucidated by extensive spectroscopic methods, including 1D and 2D NMR techniques and HRESIMS. To confirm the structure of the new compound, computational prediction of its 13 C chemical shifts was performed. All of the 17 flavonoids were reported from A. centrali - asiaticus for the first time. In addition, all flavonoids were evaluated for their antioxidant and α -glucosidase inhibitory activities. The results showed that 10 of them exhibited antioxidant activity. Meanwhile, four flavonoids displayed α -glucosidase inhibitory effect with IC50 values ranging from 38.9 to 299.7 μM. Abstract :